Hypoglycemia in patients with congenital muscle disease - Leslie H. Hayes; Pomi Yun; Payam Mohassel; Gina Norato; Sandra Donkervoort; Meganne E. Leach; Rachel Alvarez; Anne Rutkowski; Natalie D. Shaw; A. Reghan Foley; Carsten G. Bönnemann (BMC, 2020)
Abstract Background Only a few small studies have previously reported episodes of hypoglycemia in children with neuromuscular diseases; however, there has been no broader investigation into the occurrence of hypoglycemia in children with congenital muscle disease (CMD). Methods Pediatric patients enrolled in the CMD International Registry (CMDIR) with a history of hypoglycemia were included in this retrospective review. Hypoglycemic episodes and associated clinical and biochemical characteristics were characterized. Results Ten patients with CMD (5 with LAMA2-related muscular dystrophy) reported at least one episode of hypoglycemia beginning at an average age of 3.5 years. Predominant symptoms included altered mental status and nausea/vomiting, and laboratory studies demonstrated metabolic acidosis and ketonuria, consistent with ketotic hypoglycemia. Conclusion Patients with CMD may have an increased risk of hypoglycemia during fasting, illness, or stress due to their relatively low muscle mass and hence, paucity of gluconeogenic substrate. Clinicians should therefore maintain a high index of suspicion for hypoglycemia in this high-risk patient population and caregivers should routinely be trained to recognize and treat hypoglycemia.